Coopératives de production : quelle spécificité du rapport social d’activités coopératif à l’aune du rapport salarial ? - Justine Ballon; Sylvain Celle; Anne Fretel; Delphine Vallade (Revue de la Régulation)
This article analyses worker cooperatives by questioning their capacity to produce a relatively autonomous and protective social relationship of activities for their members as compared to the dominant wage labor nexus. Drawing on regulationist works on the wage labor nexus and the social relationship of activities, we propose a reading based on the conceptualization of a specific “cooperative social relation of activities”, based on the principle of double quality. This principle is characterized by four main components : (1) futurity ; (2) governance ; (3) work organization ; (4) income and mutualization. Through a historical reinterpretation and the highlighting of stylized facts, we consider the historical evolution of the “cooperative social relationship of activities” in worker cooperatives in France, in relation to the evolution of the wage labor nexus. Three main periods are identified : 1815–1910 with a “cooperative social relationship of activities” as an alternative to the emergence of the wage labor nexus ; 1910–1980 with its assimilation into the wage society ; and from the 1980s onwards with the return of an ideal bypassing wage subordination. From the perspective of this theoretical and historical approach to the “cooperative social relationship of activities”, we discuss its capacity to produce forms of social protection and wage security within the enterprise in the face of an increasingly precarious wage labor nexus. Finally, we discuss the fact that democratic governance is supposedly not only a key element of differentiation of the “cooperative social relationship of activities”, but also a condition for producing wage protection in the enterprise.